Genetic Variation in the TNF Gene Is Associated with Susceptibility to Severe Sepsis, but Not with Mortality - Song, Zhenju; Song, Yuanlin; Yin, Jun; Shen, Yao; Yao, Chenling; Sun, Zhan; Jiang, Jinjun; Zhu, Duming; Zhang, Yong; Shen, Qinjun; Gao, Lei; Tong, Chaoyang; et al. (PLOS ONE, 2012)
Background Tumor necrosis factor (TNF) and TNF receptor superfamily (TNFR)-mediated immune response play an essential role in the pathogenesis of severe sepsis. Studies examining associations of TNF and lymphotoxin-α (LTA) single nucleotide polymorphisms (SNPs) with severe sepsis have produced conflicting results. The objective of this study was to investigate whether genetic variation in TNF, LTA, TNFRSF1A and TNFRSF1B was associated with susceptibility to or death from severe sepsis in Chinese Han population. Methodology/Principal Findings Ten SNPs in TNF, LTA, TNFRSF1A and TNFRSF1B were genotyped in samples of patients with severe sepsis (n = 432), sepsis (n = 384) and healthy controls (n = 624). Our results showed that rs1800629, a SNP in the promoter region of TNF, was significantly associated with risk for severe sepsis. The minor allele frequency of rs1800629 was significantly higher in severe sepsis patients than that in both healthy controls (Padj = 0.00046, odds ratio (OR)adj = 1.92) and sepsis patients (Padj = 0.002, ORadj = 1.56). Further, we investigated the correlation between rs1800629 genotypes and TNF-α concentrations in peripheral blood mononuclear cells (PBMCs) of healthy volunteers exposed to lipopolysaccharides (LPS) ex vivo, and the association between rs1800629 and TNF-α serum levels in severe sepsis patients. After exposure to LPS, the TNF-α concentration in culture supernatants of PBMCs was significantly higher in the subjects with AA+AG genotypes than that with GG genotype (P = 0.007). Moreover, in patients with severe sepsis, individuals with AA+AG genotypes had significantly higher TNF-α serum concentrations than those with GG genotype (Padj = 0.02). However, there were no significant associations between SNPs in the four candidate genes and 30 day mortality for patients with severe sepsis. Conclusions/Significance Our findings suggested that the functional TNF gene SNP rs1800629 was strongly associated with susceptibility to severe sepsis, but not with lethality in Chinese Han population.